2010
DOI: 10.1590/s0102-311x2010000400024
|View full text |Cite
|
Sign up to set email alerts
|

Adesão a listas de medicamentos essenciais em municípios de três estados brasileiros

Abstract: This study compared the Municipal Essential Medicines Lists (REMUME)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
15

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 15 publications
0
10
0
15
Order By: Relevance
“…This result is consistent with the idea that national and local lists are compiled considering local epidemiological data and needs related to the level of health care. It is worth noting that, based on these data, the municipalities appeared to be using the list proposed nationally or, at least, they were following the same parameters for drug selection (Dal Pizzol et al, 2010). However, higher percentages were observed in other countries -99.3% in the Asia region, Saudi Arabia (Mahfouz et al, 1997), and 85% in Bangladesh (Guyon et al, 1994).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This result is consistent with the idea that national and local lists are compiled considering local epidemiological data and needs related to the level of health care. It is worth noting that, based on these data, the municipalities appeared to be using the list proposed nationally or, at least, they were following the same parameters for drug selection (Dal Pizzol et al, 2010). However, higher percentages were observed in other countries -99.3% in the Asia region, Saudi Arabia (Mahfouz et al, 1997), and 85% in Bangladesh (Guyon et al, 1994).…”
Section: Discussionmentioning
confidence: 85%
“…The criteria for inclusion of outpatient clinics were: (1) being affiliated with the Federal University of Rio Grande do Sul (UFRGS) as a research partner, (2) being located in municipalities of different sizes, categorized according to the number of inhabitants, (3) offering internships for undergraduate and/or graduate students in the health area (including residency programs), who should have access to different prescribing patterns. A detailed description of the characteristics of the municipalities and outpatient clinics participating in this study has been published elsewhere (Dal Pizzol et al, 2010).…”
Section: Description Of Research Sitesmentioning
confidence: 99%
“…According to a study performed by Dal Pizzol et al 24 , the availability of essential medicines in eight primary or secondary care services of municipalities in the central-southern region of the country was on average 88.1%, varying from 53% to 93%. Emmerick et al 20 , in a study carried out in 5 Brazilian states, reported that the national average for the percentage of prescribed drugs dispensed or administered was 67.9%, varying from 89.6% in Espírito Santo to 52.6% in Rio Grande do Sul, considering the state and from 22.0% to 93.2% considering health units analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…9 De acordo com os princípios do Sistema Úni-co de Saúde (SUS), é garantido o acesso universal e igualitário às ações e serviços públicos de saúde, incluindo aos medicamentos, previsto em 1990, e regulamentado em 1998 com a Política Nacional de Medicamentos, que teve, como propósito, assegurar a eficácia, a segurança e a qualidade dos medicamentos, a promoção do uso racional e o acesso universal àqueles considerados essenciais. 10 Na Relação Nacional de Medicamentos Essenciais (RENAME), o metoprolol foi selecionado nas formas de succinato e tartarato para o tratamento da insuficiência cardíaca (IC) graus II e III e hipertensão arterial sistêmica (HAS), respectivamente. 11 Em 2009, o succinato de metoprolol oral foi incluído na Relação Estadual de Medicamentos Essenciais do Estado da Bahia (RESME-BA), para o uso na IC e na cardiopatia isquêmica.…”
Section: Introductionunclassified